1975
DOI: 10.1136/gut.16.11.909
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in tissue ferritins in iron storage disorders.

Abstract: SUMMARY Purified tissue ferritins isolated from Bantu subjects with gross haemosiderosis, from a patient with idiopathic haemochromatosis ( HC) treated by phlebotomy, and from rats with experimental iron overload were studied in order to determine the significance of the abnormality previously demonstrated in tissue isoferritins in patients with IHC. The isoferritin profile of the tissues from the Bantu subjects and the iron-loaded rats showed a similar abnormality to that previously found in patients with unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 16 publications
1
4
1
2
Order By: Relevance
“…Acidic ferritins were demonstrated by isoelectric focusing in the four preparations from iron-loaded subjects, and these were the most prominent isoferritins in three of the four preparations. These findings do not agree with those of Powell et al (1974Powell et al ( , 1975b, who reported that with long-standing iron overload there was a loss of acidic isoferritins from heart. In our study there was no consistent pattern of isoferritin distribution, even in iron overload, and it is thus possible that the effects of iron overload are superimposed on the same type of variable isoferritin pattern as seen in the normal subjects.…”
Section: Preparationcontrasting
confidence: 94%
“…Acidic ferritins were demonstrated by isoelectric focusing in the four preparations from iron-loaded subjects, and these were the most prominent isoferritins in three of the four preparations. These findings do not agree with those of Powell et al (1974Powell et al ( , 1975b, who reported that with long-standing iron overload there was a loss of acidic isoferritins from heart. In our study there was no consistent pattern of isoferritin distribution, even in iron overload, and it is thus possible that the effects of iron overload are superimposed on the same type of variable isoferritin pattern as seen in the normal subjects.…”
Section: Preparationcontrasting
confidence: 94%
“…We first thought that, if the Drysdale (1977) hybrid scheme were correct, then some functional correlation might be expected between surface charge (a putative indicator ofthe proportions of H and L subunits) and ability to sequester iron. It has been reported that in rats and humans iron overload leads to a replacement of heart-type by liver-type ferritins in heart tissue itself (Powell et al, 1975b(Powell et al, , 1977, which might suggest a difference in ability of different ferritins to sequester iron. However, Bomford et al (1977) observed no consistent correlation between iron-loading and the proportion of L-type ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…The work showed that tissue ferritins are hybrid molecules consisting of different proportions of different subunits, with the heavy H subunit predominating in heart and the light L subunit predominating in liver. In HC, the ratio of the different isoferritins changed with the H subunit predominating, although we later showed that this was the result of tissue iron loading and it was not specific for HC . Serum ferritin differs with an extra subunit and very little iron.…”
Section: International Influencementioning
confidence: 70%
“…In HC, the ratio of the different isoferritins changed with the H subunit predominating, 10 although we later showed that this was the result of tissue iron loading and it was not specific for HC. [11][12][13] Serum ferritin differs with an extra subunit and very little iron. Its function is still unclear and the subject of current research by my colleague, Grant Ramm, at the Queensland Institute of Medical Research (QIMR; now QIMR Berghofer [vide infra]).…”
Section: International Influencementioning
confidence: 99%